Re-addressing the biosafety issues of plant growth promoting rhizobacteria - Keswani, Chetan; Prakash, Om; Bharti, Nidhi; Vílchez, Juan I.; Sansinenea, Estibaliz; Lally, Richard D.; Borriss, Rainer; Singh, Surya P.; Gupta, Vijai K.; Fraceto, Leonardo F. [UNESP]; de Lima, Renata; Singh, Harikesh B. (Elsevier, 2019)
To promote agronomic sustainability, extensive research is being carried out globally, investigating biofertilizer development. Recently, it has been realized that some microorganisms used as biofertilizers behave as opportunistic pathogens and belong to the biosafety level 2 (BSL-2) classification. This poses serious risk to the environmental and human health. Evidence presented in various scientific forums is increasingly favoring the merits of using BSL-2 microorganisms as biofertilizers. In this review, we emphasize that partial characterization based on traditional microbiological approaches and small subunit rRNA gene sequences/conserved regions are insufficient for the characterization of biofertilizer strains. It is advised herein, that research and industrial laboratories developing biofertilizers for commercialization or environmental release must characterize microorganisms of interest using a multilateral polyphasic approach of microbial systematics. This will determine their risk group and biosafety characteristics before proceeding with formulation development and environmental application. It has also been suggested that microorganisms belonging to risk-group-1 and BSL-1 category should be used for formulation development and for field scale applications. While, BSL-2 microorganisms should be restricted for research using containment practices compliant with strict regulations.
Keywords: Agriculturally important microorganisms; Biofertilizers; Biosafety; Environmental and Human Safety Index; PGPR; Sustainable agriculture